Evaluation of efficacy of submucosal tramadol after mandibular third molar surgery: a prospective pilot study - Panchal, Karan V.; Shah, Navin S.; Agrawal, Pratik; Shah, Parshwa N. (International Journal of Research in Medical Sciences, 2019)
Background: Surgical extraction of mandibular third molar is one of the most commonly performed procedure in oral and maxillofacial surgery. Its removal causes swelling, trismus, and moderate to severe pain which can be treated with various NSAID’s drugs, which have numerous side effects and gastric disturbances. In order to bypass such disturbances, Tramadol may be considered as an alternative for such patients. The aim of the study was to evaluate analgesic efficacy of submucosal tramadol and its implication over swelling and mouth opening after mandibular third molar surgery. Methods: This is a prospective study where in after post-surgical extraction of mandibular third molar, efficacy of submucosal injection of tramadol is evaluated in terms of pain and its implication over swelling and mouth opening. Results: The present study suggested there was statistically significant VAS score for pain after submucosally injecting tramadol post-surgical extraction of mandibular third molar in the following visits- 4hourly, 8hourly and 24hourly. In respect to swelling, statistically significant values was noted during 24hr and 72 h our post extraction. Also in case of mouth opening, statistically significant values were found 24 hourly. Conclusions: The present pilot study concluded that submucosal tramadol post mandibular third molar extraction has been effective in reducing pain, limiting post-extraction swelling and less impacting mouth opening by inducing less complications thereby bypassing gastric disturbances.